Measuring The Impact of Ethical Dimension in Al Reseacrh Literature: Bibliometric Study - Amin, Khoirul; Susanto, Ari (Proceeding International Conference on Religion, Science and Education, 2024)
The modern era is often associated with the development of digital technology which affects almost all aspects of human life. As time goes by and the emergence of sophisticated technology today, we are able to present creative applications in the form of artificial intelligence (AI). The presence of Artificial Intelligence (AI) is an element of technological sophistication that is phenomenal at the moment, making researchers interested in conducting in-depth and organized studies. This research uses a quantitative approach by utilizing bibliometric analysis. The aim of this research is to map the results of publications about Artificial Intelligence in the Scopus database from 1980-2023 which are reviewed in terms of main information, research development, most relevant author, most citation, countries’ scientific production, authors’ production over time, most frequent words . The results of this research show that the research data or scientific works on artificial intelligence indexed by Scopus since 198-2023 amounted to 4,477 titles, and began to experience development from 2001 to 2023. The development of research publications on the topic of artificial intelligence in the period 1981-2023 experienced fluctuating development. The institution most active in publishing scientific papers until 2023 on artificial intelligence is the University of Oxford with a total of 220 scientific papers. In the most relevant author and mos citation sections, the researcher who has the most influence and is most cited is Floridi L. Meanwhile, the country in the world that actively publishes scientific works on artificial intelligence is the USA with a total of 3279. In the Most Frequent Words section, the keywords that are frequently used in a study is artificial intelligence with 3553 uses of the word. Meanwhile, in the authors’ production over time section, Floridi L is the author who has published the most scientific works on artificial intelligence in the last 19 years.